Sedimentation Yields Long-Term Stable Protein Samples as Shown by Solid-State NMR - Wiegand, Thomas; Lacabanne, Denis; Torosyan, Anahit; Boudet, Julien; Cadalbert, Riccardo; Allain, Frédéric H.-T.; Meier, Beat H.; Böckmann, Anja (Frontiers in Molecular Biosciences, 2020)
Sedimentation of proteins into a magic-angle spinning rotor gives today access to fast and reliable sample preparation for solid-state Nuclear Magnetic Resonance (NMR), and has allowed to investigate a variety of non-crystalline protein samples. High protein concentrations on the order of 400 mg/mL are achieved, meaning that around 50-60 % of the NMR rotor content is protein, the rest is buffer solution. We herein demonstrate the long-term stability of four sedimented proteins and complexes thereof with nucleotides, comprising a bacterial DnaB helicase, an ABC transporter, an archaeal primase and an RNA polymerase subunit. Solid-state NMR spectra recorded directly after sample filling and up to five years later indicate no spectral differences and no loss in signal intensity allowing us to conclude that protein sediments in the rotor can be stable over many years. We illustrate, at the example of an ABC transporter, that not only the structure is maintained, but that the protein is still functional after long-term storage in the sedimented state.